Exploring comorbidity and pharmacological treatment patterns in psoriasis - a retrospective population-based cross-sectional study - Nelly Hamgård; Albert Duvetorp; Anna Hägg; Sandra Jerkovic Gulin; Oliver Seifert (Journal of Multimorbidity and Comorbidity)
Background Individuals with psoriasis face an increased risk of suffering from various comorbid conditions. However, there haven´t been any studies conducted in Sweden to examine the frequency of comorbidities and the corresponding treatment for these conditions among psoriasis patients. Methods The Cosmic electronic medical record represents a comprehensive repository of medical information including all residents of Region Jönköping. To conduct a population-based retrospective cross-sectional study, all individuals diagnosed with psoriasis between April 9, 2008 and July 1, 2016, were identified via the electronic medical records using ICD-10 codes. Data on comorbidity and dispensation of prescribed drugs against these comorbid conditions were analyzed. Results During the study period, 1.7% of the population (4,587 individuals) were diagnosed with psoriasis, with 74.3% of cases classified as mild to moderate psoriasis and 25.7% as severe. The remaining 268,949 individuals did not receive a psoriasis diagnosis. The study showed that psoriasis patients had higher odds of experiencing the majority of the comorbid conditions examined. Arthritis other than psoriasis arthritis was found to be the most prevalent comorbid diagnosis among psoriasis patients (adjusted OR 7.2, CI 95% 6.4-8.2, p < 0.001), followed by obesity (OR 2.4, CI 95% 1.9-3.1, p < 0,001). There was no significant difference in drug prescription for comorbid diseases between patients with psoriasis and patients without psoriasis except for arthritis and smoking cessation treatment. Conclusions Individuals with psoriasis are more susceptible to experiencing multiple comorbid conditions compared to the general population, particularly those with severe psoriasis. There is no evidence of undertreatment of comorbidity except for arthritis among psoriasis patients.